Başbakanlık Osmanlı arşiv belgeleri ışığında XIX. yüzyıl Osmanlı-Hokand Hanlığı münasebetleri - Macit, Abdülkadir (My University, 2008)
Bu tezin amacı Ortadoğu ülkelerinin Telekomünikasyon Sektöründeki Ekonomik boyutunu incelmektir. Yapılan bu araştırmada; Ortadoğu ülkelerinin Telekomünikasyon verileri sektör bazında analiz edilerek mevcut olan görünüme yorum getirilmeye çalışılmıştır. Yapılan analizler ve tablolar yardımıyla Ortadoğu Ülkelerinin Telekomünikasyon gelişim süreçleri netleştirilmeye gayret gösterilmiştir. Çalışmamızda önce iletişim ve Telekomünikasyonun tanımı ve özellikleri anlatılmaya çalışılmıştır. Daha sonra dünya ve OECD ülkelerindeki telekomünikasyon çalışmaları incelenmiş ve bunların ekonomik boyutu anlatılmaya çalışılmıştır. Ayrıca Ortadoğu ülkeleri hakkında genel bir bilgi sunulmuş daha sonra da Ortadoğu ülkelerindeki telekomünikasyon verileri üzerinde çalışılmıştır. Sonuç olarak da Ortadoğu ülkelerinin Telekomünikasyon çalışmalarının ekonomik boyutu incelenmiş ve Türkiye – Ortadoğu ülkeleri arasındaki Telekomünikasyon ilişkileri üzerine bilgiler sunulmuştur.

The Khanate of Hokand, ruled between 1710 and 1876 in Fergana area and had Hokand as its capital city, was one of the khanate among three other khanates (Boukhara, Hive) at the Turkistan region. The Hokand Khanate was founded by disassociation of the khanate from the Khanate of Boukhara and at the first time the Ottoman Empire did not welcomed its independence due to the concerns of harm against the unity of Turkistan. In the mean time, Ottoman capital, in general, received the information about the region through Boukhara’s ambassadors that the Ottoman Empire abstained the recognition of the Hokand Khanate’s sovereignty until the mid-19th Century. Thus, Mohammed Omer Khan (1809-1822) sent an ambassador to the Ottomans to recognize his rule and he requested a sword and a tuğnâme to show their approval. However, Ottoman Empire did not implement their request claiming that Hokand was part of Boukhara. It is understood that the relations between the Ottoman Empire and the Hokand Khanate got better at a later date. Khan of Hokand, Mohammed Ali Khan (1822-1842), sent an envoy to Istanbul in 1837 to ask for teachers, officers, and equipments for his army. Other Hokand delegations continued to visit Ottomans. As a result, Babıâli showed its interest in Hokand, prepared a report about the situation of Hokand and presented to the Sultan along with a cevâbnâme-i hümâyun to show their favour. Relations between the Ottoman Empire and the Hokand Khanate, developed with Mohammed Ali Khan, shaped around martial, religious, political and industrial requests of assistance and aids for ambassadors. Ottoman Empire was not able to fulfil the requests of martial, religious, political and industrial nature due to long distance, existence of Iran among the parties, the agreement between Russia at that time and continuous contention and unfair competition among the nations in Turkistan despite whole advices. However, all requests of ambassadors and appropriation of entire requests of basic educational, martial and mining related books were implemented. In spite of all, the Hokand Khanate and the Ottoman Empire continued their alliance-like existence for a century.
Keywords: Arşivler; İslam Tarihi; Osmanlı İmparatorluğu 1299-1918_Siyaset ve Yönetim